SOCIAL CAPITAL IN THE DEVELOPMENT OF KEMBANG SIALANG JOINT BUSINESS GROUP PEKANBARU CITY - Ningtias H, Septia Ayu; Susanti, Rina (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This article describes the potential of social capital in trust, networks, and norms for developing KUB Kembang Sialang business. Social capital is examined in the pattern of membership and group relationships with partners using a qualitative approach to collecting data through in-depth interviews and observations"”five informants using the purposive sampling technique and one key informant from Sialang Munggu Village. The research results show potential for social capital (with elements of trust, networks, and norms) in membership and with partners. This element of social capital plays a role in the development of group businesses by increasing cooperation between group memberships and partners, including improving order services and marketing group products in the form of wallets, mukenah (prayer clothe), masks, pencil cases, bags, tanjak, etc.